2019
DOI: 10.1016/j.coelec.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

A few key theoretical issues of importance in modern molecular electrochemistry

Abstract: This opinion paper details three typical cases in which new theoretical concepts need to be implemented in molecular electrochemistry in order to rationalize experimental results obtained in nanoscale cells or performed in new electrolytic media such as RTILs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…This can be characterized by the EDL, which usually needs to be maximized. EDLs have been shown to depend on electrode material properties (i.e., electronic structure of the metal surface, electrode surface roughness, porosity and pore size distribution), interelectrode distances and electrolyte characteristics (i.e., electrolyte concentration, viscosity and polarity, distribution of ions and solvent molecules) (Conway, 1999;Oleinick et al, 2019;Schmickler, 1996;Trasatti, 1992;Yan et al, 2017). The influence of parameters on the organic electrosorption efficiency is discussed in more detail in section 3.…”
Section: Principlementioning
confidence: 99%
“…This can be characterized by the EDL, which usually needs to be maximized. EDLs have been shown to depend on electrode material properties (i.e., electronic structure of the metal surface, electrode surface roughness, porosity and pore size distribution), interelectrode distances and electrolyte characteristics (i.e., electrolyte concentration, viscosity and polarity, distribution of ions and solvent molecules) (Conway, 1999;Oleinick et al, 2019;Schmickler, 1996;Trasatti, 1992;Yan et al, 2017). The influence of parameters on the organic electrosorption efficiency is discussed in more detail in section 3.…”
Section: Principlementioning
confidence: 99%
“…We are actually aware of only one report of a similar experimental observation, by Bard et al., [42] who observed the occurrence of an electrochemiluminescent faradaic reaction at a working electrode coupled with charging of a capacitive counter electrode. This “capacitive coupling” phenomenon has since been shown to have far reaching consequences, such as enabling single molecule cycling between two electrodes forming a closed‐gap, [43] and is expected to be ubiquitous in single molecule nano‐electrochemistry [44] . Of particular interest here, we have shown that capacitive currents can indeed be transduced into fluorescence signals by our conversions setup.…”
Section: Resultsmentioning
confidence: 77%
“…This "capacitive coupling" phenomenon has since been shown to have far reaching consequences, such as enabling single molecule cycling between two electrodes forming a closed-gap, [43] and is expected to be ubiquitous in single molecule nano-electrochemistry. [44] Of particular interest here, we have shown that capacitive currents can indeed be transduced into fluorescence signals by our conversions setup. However, there is then no perfect shape identity between the current and fluorescence signals (compare Figure 7a and 7b).…”
Section: Can a Capacitive Current Be Also Converted Into Fluorescence?mentioning
confidence: 81%
“…2,35 CV is often preferred to EIS for the study of electrochemical steps coupled with chemical reactions, whose kinetics can be measured by varying the potential scan rate. [36][37][38][39] In contrast to CV where the entire potential domain is scanned at a given scan rate, EIS offers the unique advantage of being able to perform measurements at different potentials. Interestingly, the potential dependence of the charge-transfer coefficient was inferred from EIS measurements on aromatic compounds with fast reaction kinetics, revealing a good agreement with the predicted values using the Marcus theory for outer-sphere electron transfers.…”
Section: [H1] Introductionmentioning
confidence: 99%